2021
DOI: 10.4103/iju.iju_71_20
|View full text |Cite
|
Sign up to set email alerts
|

The use of endoscopic combined intrarenal surgery as an additional approach to upper urinary tract urothelial carcinoma: Our Experience

Abstract: Introduction: With increasing experience and advancing technology, endoscopy for UTUC has become more common. Endoscopic Combined Intrarenal Surgery (ECIRS) could be an option for patients with low-grade and large-volume UTUC that could be either anatomically or technically challenging to manage by retrograde flexible ureterorenoscopy. Materials and Methods: In this video , we describe, step by step, our ECIRS technique as applied to two selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Partial pyelectomy or partial nephrectomy are extremely rarely indicated. 48,49 Common postsurgical complications include early and delayed hematuria, wound infections, ileus, incisional hernia, and pneumothorax. Ni et al, 50 showed that laparoscopic nephroureterectomy and the open technique offer similar perioperative safety and comparable oncologic efficacy.…”
Section: Clinical Managementmentioning
confidence: 99%
“…Partial pyelectomy or partial nephrectomy are extremely rarely indicated. 48,49 Common postsurgical complications include early and delayed hematuria, wound infections, ileus, incisional hernia, and pneumothorax. Ni et al, 50 showed that laparoscopic nephroureterectomy and the open technique offer similar perioperative safety and comparable oncologic efficacy.…”
Section: Clinical Managementmentioning
confidence: 99%